The protective efficacy of four iron-related recombinant proteins and their single-walled carbon nanotube encapsulated counterparts against Aeromonas hydrophila infection in zebrafish. Issue 82 (November 2018) - Guo, Zhuang; Lin, Yuexu; Wang, Xiaoyun; Fu, Yuying; Lin, Wenxiong; Lin, Xiangmin
Abstract: Iron-related proteins play important roles in iron homeostasis, and they may be potential vaccine candidates against pathogenic Aeromonas hydrophila . In addition, the encapsulation of antigens in single-walled carbon nanotubes (SWCNTs) has recently been shown to effectively stimulate the host immune response. To investigate the immune response of zebrafish to iron-related proteins and SWCNT-encapsulated proteins, we overexpressed and purified four iron-related recombinant proteins (P55870, A0KGK5, A0KPP0, and A0KIY3) from A. hydrophila . We then vaccinated zebrafish with these proteins and their SWCNT-encapsulated counterparts via both intraperitoneal injection and bath immunization. The target proteins evoked an immune response in zebrafish after intraperitoneal injection, and SWCNT-encapsulation significantly increased the immune response after bath immunization. When challenged with virulent A. hydrophila, zebrafish administered 5 μg intraperitoneal injections of SWCNT-P55870, A0KGK5, A0KPP0, or A0KIY3 had remarkably high relative percent survivals (RPSs) (50%, 55.6%, 66.7%, and 94.44% respectively). The RPSs of zebrafish vaccinated via immunization bath with 40 mg/L SWCNT-encapsulated counterparts were also high (52.94%, 55.56%, 61.11%, and 86.11%, respectively). These results indicated that zebrafish vaccinated with P55870, A0KGK5, SWCNT-P55870, and SWCNT-A0KGK5 were partially protected, while A0KPP0 and A0KIY3 were promising vaccine candidates against pathogenic A. hydrophila infection. Highlights: Four iron-related recombinant proteins were purified and encapsulated in SWCNTs. Target proteins and their SWCNT-encapsulated counterparts were vaccinated zebrafish. The immune response was increased after vaccinated.